PENILAIAN WISATAWAN TERHADAP MONUMEN PERJUANGAN RAKYAT BALI, BAJRA SANDI - Sri Suryani, Ida Ayu Putu (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2007)
Perjuangan Rakyat Bali Bajra Sandi Monument is a relatively new tourist attraction located in the center of Denpasar City. It has continuously received an increasing number of tourists' visit since it was opened in 2003. This study therefore aimed at understanding the visitor perceptions towards the monument in terms of its attractions, accessibility, facilities, and organization. The study found out that the visitors gave a very good score to the atractio11 and accessibility and good score to the facilities and organization.